Kebebasan Beragama dan Berkeyakinan di Indonesia dalam Kacamata Kebijakan Publik - Rohit Mahatir Manese (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
Abstract Freedom of religion and belief (KBB) globally has been declared in the Universal Human Right Declaration (UDHR). In Indonesia, the concept of freedom of religion and belief has long been included in the policy as the management of religion and belief in Indonesia. This KBB is understood as a set of norms derived from international law adopted by countries. In Indonesia since entering the reform era after the collapse of the new order has a fairly high commitment to human rights and KBB. This happens because the flow of democracy is large enough to create a variety of policies regarding the management of freedom of religion and belief. But on the other hand because this policy is only fully adopted without considering the context of Indonesia, it gave birth to two policy blades. Some are very radical in defending freedom of religion and belief, but on the other side there are restrictions regarding the concept of this KBB because it follows the values of the dominant religion. So this paper is here to analyze the substance of public policy. Because KBB rules are managed by policies in a democratic Indonesian state. This paper aims to analyze the process of making KBB included in public policy in Indonesia and critique the KBB concept that applies in Indonesia. In addition, this paper tries to find alternative formulations by using the Democratic model and the Deliberative Model which emphasizes that freedom of religion and belief are the right of life of citizens and are guaranteed by the state through its policies